2015
DOI: 10.1080/10495398.2014.977907
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Sequence Analyses and Phylogenetic Relationships Among Two Nigerian Goat Breeds and the South African Kalahari Red

Abstract: The first hypervariable (HV1) region of mitochondrial DNA (mtDNA) of two popular Nigerian goat breeds: West African Dwarf (WAD) (n=35) and Red Sokoto (RS) (n=37) and one exotic breed: Kalahari Red (KR) (n=38) imported from South Africa were sequenced to investigate sequence diversity, genetic structure, origin, and demographic history of the populations. A total of 68 polymorphic sites were found in 110 sequences that grouped into 68 haplotypes. Average haplotype and nucleotide diversities for all breeds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
4
13
0
Order By: Relevance
“…The new sequences in our study from Isiolo and Narok counties also proved to be extremely diverse. This finding was consistent with other genetic diversity studies on domestic goat breeds in other studies in Africa (Gorkhali et al 2014;Awotunde et al 2015). Several theories have been put forward to explain the observed high genetic diversity among these goat populations.…”
Section: Discussion Mtdna Control Region Diversitysupporting
confidence: 92%
See 3 more Smart Citations
“…The new sequences in our study from Isiolo and Narok counties also proved to be extremely diverse. This finding was consistent with other genetic diversity studies on domestic goat breeds in other studies in Africa (Gorkhali et al 2014;Awotunde et al 2015). Several theories have been put forward to explain the observed high genetic diversity among these goat populations.…”
Section: Discussion Mtdna Control Region Diversitysupporting
confidence: 92%
“…The frequency distribution of the haplogroups in all the published African goats and goats in this study was consistent with the reported patterns in other studies (Joshi et al 2004;Awotunde et al 2015), in which haplogroups A is the major component (91% of the goat haplotypes at the worldwide scale Naderi et al 2007). The different mtDNA haplogroups found in goat breeds in our study further support the previous view of multiple maternal origins of domestic goats (Chen et al 2005).…”
Section: Origins Of African Domestic Goatssupporting
confidence: 92%
See 2 more Smart Citations
“…To date, the global diversity of local goats has been assessed using various molecular tools, and such studies have been conducted in Spain (Ferrando et al., ; Manunza et al., ), Africa (Awotunde et al., ; Kibegwa, Githui, Jung'a, Badamana, & Nyamu, ; Mdladla, Dzomba, Huson, & Muchadeyi, ), the Americas (Carvalho, Paiva, Araújo, Mariante, & Blackburn, ), Europe (Bulut, Kurar, Ozsensoy, Altunok, & Nizamlioglu, ; Windig et al., ), and Asia (Lin et al., ; Nicoloso et al., ; Waki, Sasazaki, Kobayashi, & Mannen, ; Yadav, Gahlot, Gahlot, Asraf, & Yadav, ).…”
Section: Introductionmentioning
confidence: 99%